Safeguarding people living in vulnerable conditions in the COVID-19 era through universal health coverage and social protection. (January 2022) - Barron, Gabriela Cuevas; Laryea-Adjei, George; Vike-Freiberga, Vaira; Abubakar, Ibrahim; Dakkak, Henia; Devakumar, Delanjathan; Johnsson, Anders; Karabey, Selma; Labonté, Ronald; Legido-Quigley, Helena; Lloyd-Sherlock, Peter; Olufadewa, Isaac Iyinoluwa; et al.
Summary: The COVID-19 pandemic is unprecedented. The pandemic not only induced a public health crisis, but has led to severe economic, social, and educational crises. Across economies and societies, the distributional consequences of the pandemic have been uneven. Among groups living in vulnerable conditions, the pandemic substantially magnified the inequality gaps, with possible negative implications for these individuals' long-term physical, socioeconomic, and mental wellbeing. This Viewpoint proposes priority, programmatic, and policy recommendations that governments, resource partners, and relevant stakeholders should consider in formulating medium-term to long-term strategies for preventing the spread of COVID-19, addressing the virus's impacts, and decreasing health inequalities. The world is at a never more crucial moment, requiring collaboration and cooperation from all sectors to mitigate the inequality gaps and improve people's health and wellbeing with universal health coverage and social protection, in addition to implementation of the health in all policies approach.